Disorders of Consciousness A Review of Important Issues - Hakan Dogan, Kamil (IntechOpen, 2020)
Consciousness is a state of being awake and aware of one's self and surroundings according to the American Academy of Neurology. A conscious person is aware of things through thoughts and the five senses: sight, hearing, smell, taste, and touch. In disorders of consciousness, the patient has trouble being awake, or being aware, or both. Thanks to advances in science and technology, we learn new information about diseases every day. This book includes current approaches to some important issues related to disorders of consciousness.